Drivers of federal spending in pharmaceuticals of the Specialized Component: measurement and analysis - Fabiola Sulpino Vieira (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVES: Quantify and analyze the contribution of the main drivers of federal spending in pharmaceuticals purchase from the Specialized Component of Pharmaceutical Care (CEAF) in the period from 2010 to 2019. METHODS: An analysis of the annual expenditure's decomposition of the Brazilian Ministry of Health (MS) in pharmaceuticals from group 1A of the CEAF was carried out in order to isolate the contribution of its main drivers, price, quantity and residual, which involves therapeutic choices. This contribution's quantification was made with the support of the RStudio software version 1.3.1056 and the IndexNumR statistical package. RESULTS: The main driver of increased expenditure between 2011 and 2018 was the quantity of overlapping pharmaceuticals, 55% and 34%. In turn, the main driver in 2013 and 2015 was the residual, 33.2% and 57.9%. However, the expenditure in 2019 decreased by 30.4% compared with 2010. There was a decrease in the prices of daily treatments throughout the period. Among the years in which there was a reduction in expenditure, the residual was the main driver of the decrease in 2012 (-19.6%) and 2019 (-11.9%), while prices had the greatest impact on the decrease in expenditure in 2014 (-12%). There was also a reduction in the quantity of overlapping pharmaceuticals in three consecutive years, being -11% in 2015, -4% in 2016 and -11% in 2017. Lastly, in 2019 the reduction was -4%. CONCLUSIONS: The contribution of drivers to MS expenditure in the CEAF's 1A group fluctuated between 2010 and 2019. However, the expenditure decrease in recent years was induced by the three main drivers: price, quantity and residual. The decrease in the quantity purchased may have reduced the availability of some pharmaceuticals in the Brazilian Unified Health System (SUS).